Cytogenetic effects of silver and gold nanoparticles on Allium cepa roots - Priyanka Debnath; Arghadip Mondal; Amita Hajra; Chittaranjan Das; Naba Kumar Mondal (Journal of Genetic Engineering and Biotechnology, 2018)
The present study evaluates the cytogenetic effects of both silver and gold nanoparticles on the root cells of Allium cepa. In this study, the root cells of Allium cepa were treated with both gold and silver nanoparticles of different concentrations (1 mg/L, 5 mg/L and 10 mg/L) along with control for 72 h. Experimental results revealed that after 72 h of exposure, a significant decrease in mitotic index (MI) from 68% (control) to 52.4% (1 mg/L), 47.3% (5 mg/L) and 41.4% (10 mg/L) for gold nanoparticles and 57.1% (1 mg/L), 53% (5 mg/l), 55.8% (10 mg/L) for silver nanoparticles. Through minute observation of the photograph, it was recorded that some specific chromosomal abnormalities such as stickiness of chromosome, chromosome breaks, nuclear notch, and clumped chromosome at different exposure conditions. Therefore, present results clearly suggest that Allium cepa root tip assay could be a viable path through which negative impact of both gold and silver nanoparticles can be demonstrated over a wide range of concentrations. Keywords: Allium cepa, Gold nanoparticles, Silver nanoparticles, Mitotic index, Chromosomal aberrations